2001
DOI: 10.1021/bi0106336
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Biochemistry of NADH-Dependent Cytochrome b5 Reductase Are Now Consistent

Abstract: Cytochrome b5 reductase (cb5r) (EC 1.6.6.2) catalyzes the reduction of two molecules of cytochrome b5 using NADH as the physiological electron donor. The structure of pig cb5r at 2.4 A resolution was previously reported in the literature, but it was inconsistent with the biochemistry; for example, K83 and C245 were both implicated in the mechanism, but were not located at the active site. To address this problem, we have determined the structures of cb5r from rat at 2.0 A resolution and in a complex with NAD+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 36 publications
3
94
0
Order By: Relevance
“…The program Macromodel ( 51 ), with its default force fi eld OPLS 2005, a modifi ed version of the OPLS-AA force fi eld ( 52 ), and GB/SA water solvation conditions ( 53 ) were used for energy minimization. The coordinates of rat NADH-cytochrome b5 reductase (CB5R) ( 54 ), which include, in addition to the protein, a molecule of NAD + and the fl avin adenine dinucleotide (FAD) cofactor bound to the NADH and FAD binding sites, were obtained from the Protein Data Bank [(PDB) BC5R code: PDB 1IB0] ( 55 ). The structure of the protein was prepared using the Protein Preparation Wizard ( 56,57 ) included in Maestro to remove the solvent molecules, adding hydrogens, setting protonation states ( 58 ), and minimizing the energy using the OPLS force fi eld.…”
Section: Computational Dockingmentioning
confidence: 99%
“…The program Macromodel ( 51 ), with its default force fi eld OPLS 2005, a modifi ed version of the OPLS-AA force fi eld ( 52 ), and GB/SA water solvation conditions ( 53 ) were used for energy minimization. The coordinates of rat NADH-cytochrome b5 reductase (CB5R) ( 54 ), which include, in addition to the protein, a molecule of NAD + and the fl avin adenine dinucleotide (FAD) cofactor bound to the NADH and FAD binding sites, were obtained from the Protein Data Bank [(PDB) BC5R code: PDB 1IB0] ( 55 ). The structure of the protein was prepared using the Protein Preparation Wizard ( 56,57 ) included in Maestro to remove the solvent molecules, adding hydrogens, setting protonation states ( 58 ), and minimizing the energy using the OPLS force fi eld.…”
Section: Computational Dockingmentioning
confidence: 99%
“…Analysis of the crystal structure of the Physarum enzyme is now proceeding to determine the nature of the enzyme by comparing it with those of vertebrate enzymes. [17][18][19] The amino acid sequence of Physarum b5 was deduced from the nucleotide sequence determined in this study. The amino acid sequences of the other organisms were obtained from the databases through the Internet, and the sequence alignment was obtained using the ClustalW program.…”
Section: Physarum B5mentioning
confidence: 99%
“…The properties of the recombinant enzyme of P. polycephalum were, however, similar to those already reported, even though the Physarum enzyme has an about 25-residue short amino acid sequence. Based on these points, the analysis of the structure of the Physarum b5R compared with those of vertebrate b5Rs [17][18][19] is an interesting problem to be solved.…”
mentioning
confidence: 99%
“…In these enzymes, the NADPH and FAD binding regions actually represent a ferredoxin NADP ϩ reductase-like module (FNR) that is also found in transhydrogenase enzymes including ferredoxin-NADP ϩ reductase, NADH-nitrite reductase, and NADH-cytochrome b 5 reductase (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Sequence comparisons and crystallographic studies have identified some common structural motifs that participate in dinucleotide cofactor binding or impact electron transfer in the FNR-like enzymes.…”
Section: Nitric Oxide (No)mentioning
confidence: 99%